Effect of Ethanolic Extraction and Partial Purification on Phenolic Compounds Content and Antioxidant Capacities of Caesalpinia sappan Heartwood - แกนุ, ไอลดา; กองคำ, สุปราณี (Thai Journal of Science and Technology, 2021)
The effect of different ethanol concentrations and partial purification, used for the extraction of C. sappan heartwood, on the antioxidant capacity was investigated. The heartwood of C. sappan was extracted with 95%, 75%, and 50% ethanol and subsequently partitioned using deionized water, dichloromethane, and ethyl acetate. The fractions were subjected to different antioxidant assays based on free radical scavenging activity (DPPH and ABTS•+ assay) and also to lipid peroxidation assay (TBARS assay). Additionally, the content of total phenols and flavonoids was determined. The present study provides evidence that the total phenolic content and antioxidant capacity of C. sappan heartwood extracts were significantly dependent on the ethanol concentration used for extraction. However, the subsequent ethyl acetate fraction showed the overall strongest anti-oxidative activity in the chemical-based assays. In the present study, the crude extract prepared by using 75% ethanol is the best of antioxidant properties. This extract contains a considerable amount of total phenols, with inhibited DPPH and ABTS•+ free radical (low IC50 values) and inhibited lipid peroxidation on in vitro (14.21±0.47 µg/mL). Also, total phenolic content and antioxidant capacity were closely correlated (p-value <0.01).